Critiquing the scope and utility of mini-peer assessment tool in the training of medical students - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2022)
In the global vision to promote, safeguard, and maintain the health and safety of the general population and to meet the recommended standards of quality of healthcare offered, it is a must to assess the performance of medical students during their period of training. In the conventional form of medical education, assessment has predominantly been quantitative with teachers being the main stakeholder to carry out an assessment. In addition, personal views and opinion of peers or other stakeholders have also not been given due importance. However, the findings of studies have indicated that the use of mini-peer assessment tool (PAT) has played a significant role in improving the performance of students. In conclusion, the use of peers as assessors is an effective form of teaching-learning and assessment in the field of medical education. Even though there can be some extent of reluctance on the part of students, it is advisable to advocate and implement the use of mini-PAT in the training period.